2016
DOI: 10.3109/1061186x.2016.1157883
|View full text |Cite
|
Sign up to set email alerts
|

Oral bioavailability of curcumin: problems and advancements

Abstract: Curcumin is a natural compound of Curcuma longa L. and has shown many pharmacological activities such as anti-inflammatory, anti-oxidant in both preclinical and clinical studies. Moreover, curcumin has hepatoprotective, neuroprotective activities and protects against myocardial infarction. Particularly, curcumin has also demonstrated favorite anticancer efficacy. But limiting factors such as its extremely low oral bioavailability hampers its application as therapeutic agent. Therefore, many technologies have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
285
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 451 publications
(291 citation statements)
references
References 70 publications
1
285
0
5
Order By: Relevance
“…Second, the relatively high dose of curcuma used in our study induced moderate effects on serum hepcidin probably due to the low oral bioavailability of curcumin. Therefore, new formulations of curcuma with enhanced oral bioavailability should be tested in further studies . Third, one could argue that glucose was used as placebo in our study despite recent published data that showed links between glucose, insulin metabolism, and hepcidin .…”
Section: Discussionmentioning
confidence: 94%
“…Second, the relatively high dose of curcuma used in our study induced moderate effects on serum hepcidin probably due to the low oral bioavailability of curcumin. Therefore, new formulations of curcuma with enhanced oral bioavailability should be tested in further studies . Third, one could argue that glucose was used as placebo in our study despite recent published data that showed links between glucose, insulin metabolism, and hepcidin .…”
Section: Discussionmentioning
confidence: 94%
“…To overcome these problems several approaches are being developed like encapsulation of Cur in liposomes and polymeric micelles, formation of inclusion complexes and polymeric conjugates, and synthesis of new heterocyclic Cur derivatives and analogs (Liu et al, 2016). An efficacious solution to the bioavailability issue is needed to ensure appropriate tissue exposures of this natural product in clinical investigation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These physicochemical properties contribute to a low intestinal absorption and rapid metabolism of curcumin, thereby resulting in a low systemic bioavailability. While the biological activity of curcumin metabolites has been demonstrated, low plasma levels of parent compound is generally referred to as a main reason to explain the lack of complete translation of experimental findings on the anti‐tumor effects of curcumin to clinical practice (Kharat, Du, Zhang, & McClements, ; Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%